2001
DOI: 10.1353/sof.2001.0063
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement, Stress, and Mental Health: Findings from the 1995 Detroit Area Study

Abstract: Although interest in the links between religion and mental health has increased sharply in recent years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
369
5
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(406 citation statements)
references
References 98 publications
21
369
5
2
Order By: Relevance
“…Religious attendance is consistently higher among Blacks than Whites (Taylor, Chatters, Jayakody, & Levin, 1996). In turn, numerous studies have shown that religious attendance is associated with increased levels of subjective well-being and lower psychological distress and mental illness in general (Ellison, Boardman, Williams, & Jackson, 2001) and in the Black community (Ellison, 1995). Future research is likely to show that religion is a protective factor for Blacks in the face of inequality and discrimination.…”
Section: What Might Explain the Resilience In The Black Community?mentioning
confidence: 90%
“…Religious attendance is consistently higher among Blacks than Whites (Taylor, Chatters, Jayakody, & Levin, 1996). In turn, numerous studies have shown that religious attendance is associated with increased levels of subjective well-being and lower psychological distress and mental illness in general (Ellison, Boardman, Williams, & Jackson, 2001) and in the Black community (Ellison, 1995). Future research is likely to show that religion is a protective factor for Blacks in the face of inequality and discrimination.…”
Section: What Might Explain the Resilience In The Black Community?mentioning
confidence: 90%
“…Alongside this positive facet of faith in building resilience against traumas and traumatic life events, there is also research that points out the unfavourable aspect of faith [35,36]. These scholars have shown that it can also have a negative impact on resilience: it may have the potential to increase levels of fear, anxiety, or stress when perceptions and understandings of faith (and religion) rest upon negative feelings and beliefs.…”
Section: Faith Resilience In Everyday Lifementioning
confidence: 99%
“…In fact, rival bodies of scholarship have emerged. One stream of research has indicated a persistently null association between prayer and mental health (Ellison 1991;Ellison et al 2009;Schieman et al 2006), while another has linked prayer to adverse mental health conditions (Bradshaw et al 2008;Ellison 1995;Ellison et al 2001) ).…”
Section: Empirical Backgroundmentioning
confidence: 99%